Nursing Students’ Perceptions about the Effects of Climate Change on Health: A Descriptive Exploratory Study - Santos, Jonalyn P.; Gumabay, Eladio Martin S. (Department of Nursing, Faculty of Medicine, Universitas Diponegoro, 2024)
Background: Climate change is recognized as an important health concern that the health sector and nurses must prepare for. Adequate preparation and understanding of its effects on health must be exemplified by nurses and nursing students. Previous studies showed that nurses and nursing students have good knowledge of climate change and its effects on health. However, none of these studies were conducted in the Philippines.Purpose: This study explored the perceptions of nursing students about the effects of climate change on health.Methods: The researchers utilized a descriptive qualitative research design. The study was conducted among level three Bachelor of Science in Nursing students selected through purposive sampling using the following criteria: a) students who were enrolled with a full load of units in the BSN course, and b) those who have not taken Disaster Nursing course in the previous semesters. A total of 35 participants were included in the study. Data collection was done through an interview using a researcher-made interview guide. Data analysis was done through content analysis.Results: Two major themes were identified, which describe the perceptions of the nursing students about the effects of climate change on health. The findings revealed that the respondents have an adequate understanding of what climate change is and the factors that cause it. The respondents also mentioned that climate change negatively affects the physiological health of humans. Specifically, climate change increases the risk for non-communicable disease such as cardiovascular and respiratory diseases. It also alters certain characteristics of communicable diseases such as prevalence, seasonal pattern, and geographic distribution.Conclusion: The findings revealed that student nurses know what climate change is and are aware that it negatively affects health. However, their perceptions of the effects of climate change on health are limited to its physiologic effects, specifically on non-communicable and infectious disease, as this reflects their understanding of how environmental factors affect disease pathogenesis or development.